2017
DOI: 10.3311/ppci.10749
|View full text |Cite
|
Sign up to set email alerts
|

Parametric and Comparative Study of a Flexible Retaining Wall

Abstract: IntroductionThe design of retaining walls in day-to-day practice is currently based on different calculation methods. If classical methods considering specific modes of failure, the elastic line and the equivalent beam are still employed for certain types of walls, it is mainly the subgrade reaction and the numerical methods which are most frequently adopted. The subgrade reaction method or spring method is rather well mastered and uncertainties mainly rely in the choice of the coefficient of subgrade reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…4). After the geotechnical finite element analysis, the effects and displacements acting on the structure were transformed to the structural model, which was created using Axis VM finite element software, which is a widespread (especially in Hungary) special finite element software for structural engineers [9]. After a few rounds of iteration, which approximately means a few hundred hours of modelling a configuration, which can be said to be optimum was reached.…”
Section: Modelling Of Structural Elementsmentioning
confidence: 99%
“…4). After the geotechnical finite element analysis, the effects and displacements acting on the structure were transformed to the structural model, which was created using Axis VM finite element software, which is a widespread (especially in Hungary) special finite element software for structural engineers [9]. After a few rounds of iteration, which approximately means a few hundred hours of modelling a configuration, which can be said to be optimum was reached.…”
Section: Modelling Of Structural Elementsmentioning
confidence: 99%
“…Past research works have also been conducted to incorporate the uncertainty of soil properties in the retaining wall design. Chogueur et al [27] presents various simulations with the structure installed into the supported ground without surcharge. They concluded that the use of computational methods minimizes uncertainties arising from limited number of soil properties.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in literature investigated the evolution of lateral pressures and the formation of shear bands in retained backfills. Some of these used experiments [4][5][6][7][8][9][10][11] whereas the others preferred numerical methods [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%